A TRAJETÓRIA E PAPEL DOS COREDES NO DEBATE SOBRE O DESENVOLVIMENTO REGIONAL NO RIO GRANDE DO SUL - Ribas, Taciana Angélica Moraes; Allebrandt, Sérgio Luís; Krüger, Roseli Fistarol; Prediger, Reneo Pedro; Ribas, João Vitor Moraes (Salão do Conhecimento, 2019)
Projeto de pesquisa realizado no GPDeC/PPGDR/UNIJUI